What causes stress incontinence: Fallacies, fascias and facts - DeLancey, John (Canadian Urological Association Journal, 2012)
The traditional view of the pathophysiology of stress urinary incontinence (SUI) was that a loss of urethral support was the primary abnormality present. Recent research has challenged this hypothesis, demonstrating that impaired urethral function plays the key causative role. Improving our understanding of the underlying pathologic mechanisms is important to identifying the cause of treatment failures and for developing novel therapies to treat SUI.